Notes on Prado's position regarding the Brazilian feudalism thesis (Ágora Journal, 2022)
This work intends to expose and analyze the position of Caio Prado Jr. about the thesis of feudalism in Brazil. Defended by the expressive majority of the intellectual groups of the Brazilian Communist Party (PCB) at the time of the quarrel, this thesis sought to sustain the existence of a certain degree of feudal traits in the colonization of Brazil and, consequently, of “feudal remnants” to be eliminated in the present. Dissatisfied with such interpretation and its implications in terms of political strategy, Prado Jr., through a rigorous study of the Brazilian past, comes to the conclusion that there could not have been something similar to a “feudalism” in our process of political-economic evolution. Beyond revisiting the debate in its original form, I will seek, throughout the text, to dialogue with a series of theoretical developments of the Pradian position. I believe that this will be useful, on one hand, to verify the longevity of Caio Prado's interpretation; on the other, and more importantly, to discuss how his ideas might be revisited in light of the latest developments in this field of study.
Keywords: Caio Prado Jr.; Feudalism in Brazil; Mode of production